ANALISIS PERSONAL BRANDING ENTREPRENEURSHIP SANDIAGA SALAHUDDIN UNO DALAM MENUMBUHKAN MOTIVASI BERWIRAUSAHA MAHASISWA UNIVERSITAS MERCU BUANA - Faridinah Azzah; A. Rahman HI A. Rahman HI (Universitas Mercu Buana, 2020)
An entrepreneur builds Personal Branding to advance his business and image, by publishing self-contained content in social media so that he can push himself into a new market. This research aims to find out Top Of Mind, Sandiaga Salahuddin Uno's Personal Branding Entrepreneurship and the entrepreneurial motivation of Mercu Buana University students regarding Personal Branding Sandiaga Salahuddin Uno. The method used in this research is descriptive method using the process of collecting interview data, documentation and literature study. The results of the study have suggestions for Sandiaga Salahuddin Uno, to remain an inspiring figure for the Indonesian people, maintain and remain himself, grounded and inform the knowledge of business and entrepreneurship.